PERANCANGAN COMPANY PROFILE SEBAGAI MEDIA PROMOSI PADA SP-PLAST SABLON UNGARAN BERBASIS MULTIMEDIA INTERAKTIF - Rafika Ade Ristiyawati (STEKOM PRESS, 2018)
SP-Plast screen printing is a company engaged in the field of printing that uses tools or screen printing media. Company profile is a promotional media that can be used to support promotions that already exist on screen printing SP-Plast. Based on sales data available on SP-Plast screen printing, there was a decrease in the number of sales from March - May 2017. SP-Plast screen printing requires a media to help more attractive promotions to attract clients and keep customers from switching to other companies without eliminating the previous promotional media, namely with an interactive multimedia company profile. Company profile can be used to improve the presentation of company identity which was previously still in the form of print media, namely banners and business cards. The results of this design in the form of an interactive multimedia-based company profile that contains the history, vision & mission, screen printing production processes, contacts, and addresses SP-Plast screen printing. The results of this study are based on the validation test assessment of users is 3.13. These criteria are in the range of 2.51 - 3.25 which is included in the effective category, so this company profile tool can be said to be feasible.